Methodology for the motor coordination through the adapted table tennis in boys and girl with Down´s Syndrome - Carlos Alberto Govea Macía; Ismary Mencho Moreno (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2014)
The present research approaches the application of a pre experiment with the objective of elaborating a methodology that stimulates the development of the motor coordination, adapting the table tennis to the necessities and characteristics of the boys and girls with Downs Syndrome diagnose. To elaborate it was started from the deficiencies and contradictions found in the adapted sport for patients with Down's Syndrome, as well as the potentialities and deficiencies in their motor coordination; there are used methods and techniques of theoretical character (analysis, synthesis, induction, deduction, hypothetical, deductive, systemic structural functional and modeling); of empiric-experimental character (observation, measurement, documental analysis, experts' approach, pre pedagogic experiment, study case; and as techniques: the survey and instruments; and of mathematical-statistical character, descriptive statistic and inferential. The use of the experts' criterion is used to verify the theoretical validity elements of the designed methodology. The results analysis allows accepting the proposal as valid after having obtained the theoretical and practical results validation with a case study implementation.